Re-Forming the Past : History, The Fantastic, and the Postmodern Slave Narrative - Spaulding, A. Timothy (Book collections on Project MUSE., 2005)
"In Re-Forming the Past, A. Timothy Spaulding examines contemporary revisions of slave narratives that use elements of the fantastic to redefine the historical and literary constructions of American slavery. In their rejection of mimetic representation and traditional historiography, postmodern slave narratives such as Ishmael Reed's Flight to Canada, Octavia Butler's Kindred, Toni Morrison's Beloved, Charles Johnson's Ox Herding Tale and Middle Passage, Jewelle Gomez's The Gilda Stories, and Samuel Delany's Stars in My Pocket Like Grains of Sand set out to counter the usual slave narrative's reliance on realism and objectivity by creating alternative histories based on subjective, fantastic, and non-realistic representations of slavery. As these texts critique traditional conceptions of history, identity, and aesthetic form, they simultaneously re-invest these concepts with a political agency that harkens back to the original project of the 19th-century slave narratives." "In their rejection of mimetic representation and traditional historiography, Spaulding contextualizes postmodern slave narrative. By addressing both literary and popular African American texts, Re-Forming the Past expands discussions of both the African American literary tradition and postmodern culture."--Jacket